2021
DOI: 10.1021/acs.organomet.0c00814
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II) N^O Chelating Complexes Catalyzed One-Pot Approach for Synthesis of Quinazolin-4(3H)-ones via Acceptorless Dehydrogenative Coupling of Benzyl Alcohols and 2-Aminobenzamide

Abstract: A convenient protocol for the one-pot synthesis of quinazolin-4(3H)-ones using palladium(II) complexes via dehydrogenative coupling of readily available benzyl alcohols and 2-aminobenzamide has been described. New structurally related Pd(II) N^O chelating complexes of general configuration [Pd(L)Cl(PPh 3 )](where L = dimethylamino benzoylhydrazone ligands) have been designed and synthesized. The formation of the complexes has been recognized by analytical and spectral methods (FT-IR, NMR& HR-MS). The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…An interesting protocol involves the cyclocondensation of aryl aldehydes with anthranilamide towards a library of 2,3-dihydroquinazolin-4(1H)-ones. [17][18][19] In this method, anthranilamide is considered as a green reagent because, on the basis of the cyclic mechanism, this reaction gives only water as the by-product. 20 In order to derive the mentioned reactions, acid catalysts which dominate these reactions can be regarded as standard methods, evaluating the reactivity of Brønsted-Lowry acid species as potential catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting protocol involves the cyclocondensation of aryl aldehydes with anthranilamide towards a library of 2,3-dihydroquinazolin-4(1H)-ones. [17][18][19] In this method, anthranilamide is considered as a green reagent because, on the basis of the cyclic mechanism, this reaction gives only water as the by-product. 20 In order to derive the mentioned reactions, acid catalysts which dominate these reactions can be regarded as standard methods, evaluating the reactivity of Brønsted-Lowry acid species as potential catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three complexes, we found that complex 2 was the most effective catalyst for this reaction because the electron‐donating group (–OCH 3 ) enhances the catalytic activity. [ 22 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the X-ray structure of 4a was presented in Supporting Information. Next, we developed various alkyl primary amines (3). Butylamine was added to this reaction mixture, and it displayed moderate yield (76% for 5a).…”
Section: Scheme 1 Synthesis Of 2-aminobenzamidesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] These skeletons could be easily synthesized from 2-aminobenzamides. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Besides, these 2-aminobenzamides scaffolds also exist in various biological active agents such as anticancer, antimicrobial, anti-inflammatory, anticonvulsant, anti-tubercular, antiviral, and antimalarial agents. 1,6,9,11 Therefore, the synthesis of 2-aminobenzamides plays an important role in organic synthesis.…”
mentioning
confidence: 99%